Development of a Practical Tool for the Assessment of Biological Performances in Wastewater Treatment Plants. Issue 11 (21st July 2016) - Malinverni, Francesca F.; Genon, Giuseppe; Ruffino, Barbara
Abstract : The presence of residual nitrogen loads in treated wastewater may cause eutrophication in receiving water bodies. Nitrogen removal in wastewater treatment plants (WWTPs) is commonly based on nitrification–denitrification (NdN). This study presents a novel and practical assessment tool which uses mass balances to evaluate the efficiencies of the NdN processes in WWTPs. The tool was tested on a WWTP with a capacity of 137 000 population equivalent. A 6 year (2008–2013) survey of the plant demonstrated that the NdN compartment was not able to guarantee the annual average of 80% for the total nitrogen (TN) removal. This figure is fixed by the local wastewater regulation. From the survey data, the values of the kinetic constants for the processes of biochemical oxygen demand oxidation, nitrification, and denitrification were calculated. With these values the influence of the process parameters ( i.e ., recycle ratio of the aerated mixture, flow rate, biomass concentration) and plant parameters (volume of the nitrification and denitrification ponds) on the efficiency of TN removal was evaluated. The results of the sensitivity analysis revealed that an intervention on process or plant parameters was not sufficient to reach the requested target of TN removal. Consequently, the introduction of a post‐denitrification module was suggested. Abstract : A new and practical tool for the efficiency assessment of nitrification/denitrification processes is developed and tested on a wastewater treatment plant (WWTP). The proposed tool uses mass balances referring to the biological compartments of the WWTP. In the considered case‐study an intervention on process or plant parameters is not sufficient to reach the requested target of total nitrogen removal.